Pengelolaan Sampah Plastik Bertenaga Surya di Kawasan Wisata Megalitikum Gunung Padang Cianjur - Aris Budi Setyawan; Tri Mulyanto; Heru Kuncoro (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
As a prehistoric site of Megalithic culture in West Java dating back 10,000-25,000 BC, Gunung Padang is a highly potential tourist attraction. The uniqueness of this tourist area attracts many tourists, both local and foreign, to visit. In addition to bringing positive economic impacts to the community through the sale of various local products such as palm sugar, honey, souvenirs, and homestay businesses around the tourist area, the local government also receives additional income through levies imposed on visitors. On the other hand, the arrival of tourists also results in waste generated from tourist activities while in the Gunung Padang tourist area. So far, Pokdarwis has been trying to handle the waste by collecting, stockpiling, and burning it. This method is certainly not a solution that can be continued in the long term. This community service activity was carried out to provide a better understanding of proper waste management and to provide solar-powered waste processing machines, considering that the Gunung Padang tourist site has great potential for solar energy as an energy source.